Moisture Removal Rate in A Solar Powered Liquid Desiccant Air Conditioning System (University of Khartoum Engineering Journal, 2022)
Air conditioning is an energy intensive process, especially in hot and humid climates. Therefore, more research and development of solar alternatives to conventional space conditioning technique are desirable both in terms of overall cost saving and minimizing the environmental impact. The main disadvantage of vapor-compression air-conditioning systems is that they are thermodynamically inefficient. The handling of the latent load requires cooling of the air below its dew point, and thus additional energy is needed to reheat the air to the delivery temperature. Liquid desiccant air-conditioning systems remove the latent load directly from the air by absorbing the moisture using liquid desiccant solution. The liquid desiccant is then regenerated again using low grade heating source like solar energy. In addition to dehumidification, an added benefit of some desiccants is their ability to absorb inorganic and organic contaminants in air. Moreover, the absorption process has the potential to remove biological pollutants such as bacteria, fungi, and viruses, improving indoor air quality. This paper experimentally studied the moisture removal rate in a solar powered liquid desiccant air conditioning system using Triethylene Glycol (TEG) as a desiccant. An evacuated tube solar boiler was used for desiccant regeneration. During the experimental investigation, inlet parameters, including air flow rate, humidity ratio, desiccant flow rate, and concentration were varied. The effect of these variables on the moisture removal rate was studied. It was found that the moisture removal rate increases with increasing the inlet air flow rate, inlet air humidity ratio, desiccant flow rate, and desiccant solution concentration.